Obtencion de una cepa pura vacunal de Eimeria acervulina I. Patogenicidad - Szczypel, B.=700 1 Perez, A.; Larramendy, R.; Saldivar, L.; Mendez, G.; Reiners, A.
(En, Es)
Ilus., 6 ref.
Keywords: AVES DE CORRAL; COCCIDIOSIS; ENFERMEDADES PARASITARIAS; PATOGENICIDAD; EIMERIA ACERVULINA; VACUNA; CUBA; REVISTA CUBANA DE CIENCIA AVICOLA